2016
DOI: 10.1016/j.pmedr.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity pattern, cardiorespiratory fitness, and socioeconomic status in the SCAPIS pilot trial — A cross-sectional study

Abstract: Living in a low socioeconomic status (SES) area is associated with an increased risk of cardiovascular events and all-cause mortality. Previous studies have suggested a socioeconomic gradient in daily physical activity (PA), but have mainly relied on self-reported data, and individual rather than residential area SES. This study aimed to investigate the relationships between residential area SES, PA pattern, compliance with PA-recommendations and fitness in a Swedish middle-aged population, using objective mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 44 publications
4
28
0
Order By: Relevance
“…Studies [ 53 , 54 ] reporting on the association between CRF and residential area SES conducted multivariable regression analysis and observed that median VO 2 max increased and odds of low fitness (METs) decreased with higher residential area SES.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [ 53 , 54 ] reporting on the association between CRF and residential area SES conducted multivariable regression analysis and observed that median VO 2 max increased and odds of low fitness (METs) decreased with higher residential area SES.…”
Section: Resultsmentioning
confidence: 99%
“…In this systematic review and meta-analysis of the association between SES and CRF in adults, evidence from 15 population-based studies from 8 different countries, shows that predominately higher SES is associated with increased CRF. Socioeconomic exposures, such as SES indices, composed of various SES indicators [ 50 , 52 ], and residential area SES [ 54 ], generally showed a positive relationship with CRF [ 41 , 53 ]. Studies using education level as an exposure, showed either a positive relationship between education and CRF [ 41 – 45 , 47 , 48 , 51 ] or a u-shaped relationship [ 46 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Mexican found an inverse association between active life style and car use, and that lower SES groups walk, cycle or use public transport when commuting [ 32 ]. Another study suggested that lower socioeconomic groups were less active in MVPA which was closely related to the characteristics of their place of residence [ 33 ]. Thus, studies examining associations between physical activity and socioeconomic status should consider both the physical activity domains assessed as well as the locations where activity take place.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, due to their greater health awareness, they adhere better to the practice of physical activity. This may have contributed to the fact that their BMI values are lower, with consequent lower prevalences of obesity and higher HDL-cholesterol 27 .…”
Section: Discussionmentioning
confidence: 99%